VR sculpting as a therapeutic intervention for alleviating anxiety: a case study from a university art class - Huan Ding; Huan Ding; Bo Lin; Bo Lin; Yuwei Xu; Dunjiang Shang; Yi Han (Frontiers in Psychiatry)
BackgroundAnxiety among university students has become increasingly prominent in higher education settings, adversely affecting not only their academic performance but also their overall mental health. While medication and psychological interventions can help alleviate anxiety to some extent, it is crucial for this particular group to find more convenient, easily accepted non-pharmacological approaches. Art therapy, especially hands-on creative activities, is considered an effective means of regulating anxiety, yet research on virtual reality (VR) sculpting remains relatively scarce.ObjectiveThis paper aims to investigate the therapeutic effects of VR sculpting on college students’ anxiety levels and assess its impact on psychological well-being and physiological relaxation, as measured by heart rate variability (HRV).MethodsThe study recruited 30 undergraduates, evaluating their anxiety levels via the Generalized Anxiety Disorder scale (GAD-7), psychological well-being via the Positive and Negative Affect Schedule (PANAS), and physiological relaxation via HRV. Subsequently, we monitored how VR-based artistic sculpting influenced changes in GAD-7, PANAS, and HRV scores.ResultsComparing the data before and after the art-based intervention revealed a significant decrease in participants’ GAD-7 scores, a substantial rise in PANAS scores indicating enhanced psychological well-being (p < 0.05), and a marked increase in HRV, suggesting VR sculpting can promote physiological relaxation. Qualitative interviews further showed that most participants experienced strong focus and emotional release during the VR sculpting process.ConclusionAs a non-pharmacological art therapy method, VR sculpting demonstrates a notably positive effect on reducing anxiety and improving mental well-being among university students. This study provides compelling evidence for using art therapy to address mental health issues in a college environment. Future research should consider longer intervention periods and more varied measures to further investigate the long-term effectiveness and broader applicability of this approach.